DESENVOLVIMENTO DE APLICATIVO PARA MONITORAMENTO REMOTO ATRAVÉS DE EQUIPAMENTOS MÓVEIS - Faccin, Luis F.; Padoin, Edson L.; Dill, Sérgio L.; Sausen, Paulo S.; Campos, Maurício d. (Salão do Conhecimento, 2013)
Resumo